450 nm GaInN ridge stripe laser diodes with AlInN/AlGaN multiple cladding layers. (23rd May 2019) - Arakawa, Kei; Miyoshi, Kohei; Iida, Ryosuke; Kato, Yuki; Takeuchi, Tetsuya; Miyoshi, Makoto; Kamiyama, Satoshi; Iwaya, Motoaki; Akasaki, Isamu
Abstract: We investigated and improved optical waveguides along the vertical and horizontal directions in 450 nm GaInN laser diodes. As a result, we demonstrated a low threshold current density (1.15 kA cm −2 ) of a GaInN ridge stripe laser diode containing a 3-pair 40 nm Al0.82 In0.18 N/25 nm Al0.03 Ga0.97 N multiple bottom cladding layer at room temperature under pulsed condition. This threshold current density is smaller than our typical value with a 1  μ m Al0.03 Ga0.97 N bottom cladding layer. AlInN/AlGaN multiple layers are useful as n-type cladding layers in visible laser diodes to achieve higher optical confinement factors while smooth surfaces were obtained.